2021
DOI: 10.1101/2021.09.13.460064
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High interaction valency ensures cohesion and persistence of a microtubule +TIP body at the plus-end of a single specialized microtubule in yeast

Abstract: Microtubule plus-end tracking proteins (+TIPs) control microtubule specialization and are as such essential notably during eukaryotic cell division. Here, we investigated interactions and functions of the budding yeast Kar9 network consisting of the core +TIPs components Kar9 (functional homologue of APC, MACF, and SLAIN), Bim1 (orthologue of EB1), and Bik1 (orthologue of CLIP-170). Our data indicate that a redundant, multivalent web of interactions links the three +TIPs together to form a "Kar9 body" at the t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
6
1
0
Order By: Relevance
“…Further studies will be necessary to investigate whether additional +TIPs contribute to the formation and regulation of +TIP-droplets. Our work here and recent studies demonstrate that +TIP networks can behave like liquid condensates (Wu et al, 2021;Maan et al, 2021;Meier et al, 2021;Song et al, 2021). This work adds to the growing list of microtubule-related processes that are driven by LLPS and provides an exciting new paradigm for how cells can spatiotemporally control microtubule dynamics through local tubulin concentration (Zhang et al, 2015;Woodruff et al, 2017;Hernández-Vega et al, 2017;King and Petry, 2020;Jiang et al, 2021;Maan et al, 2021;Meier et al, 2021;Song et al, 2021).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Further studies will be necessary to investigate whether additional +TIPs contribute to the formation and regulation of +TIP-droplets. Our work here and recent studies demonstrate that +TIP networks can behave like liquid condensates (Wu et al, 2021;Maan et al, 2021;Meier et al, 2021;Song et al, 2021). This work adds to the growing list of microtubule-related processes that are driven by LLPS and provides an exciting new paradigm for how cells can spatiotemporally control microtubule dynamics through local tubulin concentration (Zhang et al, 2015;Woodruff et al, 2017;Hernández-Vega et al, 2017;King and Petry, 2020;Jiang et al, 2021;Maan et al, 2021;Meier et al, 2021;Song et al, 2021).…”
Section: Discussionsupporting
confidence: 76%
“…The role of different mammalian EB family members in regulating LLPS will be an interesting direction for future studies. The ability of these +TIP-networks to phase separate depends on intrinsically disordered regions (Maan et al, 2021;Song et al, 2021) and multivalent interaction modules (Figure 2; Meier et al, 2021), consistent with the observation that these features are highly evolutionarily conserved across +TIPs (Wu et al, 2021). Further studies will be necessary to investigate whether additional +TIPs contribute to the formation and regulation of +TIP-droplets.…”
Section: Discussionsupporting
confidence: 63%
“…Our work here and recent studies demonstrate that +TIP networks can behave like liquid condensates (Wu et al, 2021;Maan et al, 2021;Meier et al, 2021;Song et al, 2021). This work adds to the growing list of microtubule-related processes that are driven by LLPS and provides an exciting new paradigm for how cells can spatiotemporally control microtubule dynamics through local tubulin concentration (Zhang et al, 2015;Woodruff et al, 2017;Hernández-Vega et al, 2017;King and Petry, 2020;Jiang et al, 2021;Maan et al, 2021;Meier et al, 2021;Song et al, 2021). Interrogating the mechanical properties and composition of +TIP-droplets, as well as studying their regulation throughout the cell cycle, will be exciting avenues for future research.…”
Section: Discussionsupporting
confidence: 76%
“…Is phase separation a common feature of +TIPs? Studies performed in parallel to our work show that this phenomenon is conserved across evolution: +TIPs in budding yeast, fission yeast, and higher eukaryotes have recently been demonstrated to undergo phase separation (Maan et al, 2021;Meier et al, 2021;Song et al, 2021, Jijumi et al, 2022. Intriguingly, in line with our results, the yeast studies confirmed that the CLIP-170 homolog played a key role in the phase separation process, whereas LLPS potency of EB homologs varied between organisms.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation